Analisis Risiko dan Perilaku Pencegahan Penyakit DM Tipe 2 Pada Usia Produktif di Wilayah DKI Jakarta Tahun 2021 - Setiawaty, Savanna; Risma Dianti, Anggi Risma Dianti; Noviyanti, Shabrina Rahmi (Journal of Public Health Education, 2022)
Introduction: Diabetes Mellitus type 2 is a type of diabetes mellitus that often occurs in society, accounting for about 90% of cases of insulin production that are inadequate and total inability to respond to insulin known as insulin resistance. Type 2 DM is more common in parents, but more common in children, adolescents, and early adults. Diabetes Mellitus is a chronic disease and is the fourth leading cause of death in Indonesia. The prevalence of Indonesian people with Diabetes Mellitus is 1.5%. For the Jakarta region in 2018, the prevalence of Diabetes Mellitus was the first order in Indonesia which was 26%. Objectives: This research population is a community in the district of DKI Jakarta with a sample of 599 respondents who filled in the online quiz using the Google form. Method: Research was done in March-August 2021, with a kind of qualitative research descriptive using first-reserved data using the online quiz (google form) and secondary data obtained from 2018 RISKESDAS and Profil Kesehatan Kota DKI Jakarta 2018. Result: Research results show that the majority of people in Jakarta still smoke actively (52%) and are passive smokers (48%), those who do not do as much physical activity (24.7%), and those with poor eating patterns (25.8%).